ANALISIS TERHADAP VARIASI RELEVANSI-NILAI INFORMASI AKUNTANSI DI INDONESIA: PENGUJIAN HIPOTESIS INFORMASI ALTERNATIF - Margani Pinasti (Journal of Indonesian Economy and Business (JIEB), 2006)
This research examines factors that explain the variation of value-relevance of accounting information for stock market in Indonesia. A hypothesis namely alternative information hypothesis was proposed in the study. In the alternative information hypothesis, researcher argues that value-relevance of accounting information is getting decreasing from time to time because of the response change of the users on accounting information, as the result of alternative information that is available and used in the company valuation nowadays. To examine the alternative information hypothesis, examining the value-relevance variation of accounting information between the time and between the factors of company characteristic is done. Industry factors, negative earnings, one-time items are examined, to find out whether those factors are able to explain the variation of the value-relevance of accounting information. The period of study samples are from 1990 to 2001. The analysis uses five models of company valuation and two kinds of value-relevance measures, those are R2 and abnormal pricing errors. The results of this study proved that there is decreasing of value-relevance of accounting information from time to time. Industry variable and transitory earnings variables (negative earnings characteristic and one-time items proportion) can not explain the variation of value-relevance of accounting information. Overall, this research can draw conclusion that for stock market in Indonesia, there has been decreasing of value-relevance of accounting information from time to time. It can not be attributed to the industry variable, negative earnings characteristic, or one-time items proportion. So that, the decreasing is explained by the lower value-relevance of accounting information from time to time, which reflects the users response on accounting information. This study results support the alternative information hypothesis.